A STRUGGLE TO LIVE IN ANTHONY MINGELLA’S COLD MOUNTAIN MOVIE 2003: A PSYCHOANALYTIC APPROACH - ARDI, DENI ROBI (2010)

(untitled)
The problem of the study is to reveal how the struggle for live of the major character reflected in Anthony Mingella’s Cold Mountain. The objectives of the study are to analyze the structural element of the movie and to analyze the character of Ada based on individual psychological perspective. This study is descriptive qualitative research. The object of the study is Cold Mountain film directed by Anthony Mingella. The data sources are divided into two namely primary data source and secondary data source. The primary data source is the film itself and the secondary data is the other sources related to the analysis including the script text. The techniques of data collection are watching the movie, reading the script and observe the library research. The technique of data analysis is descriptive analysis. The results of the research shows that first is in structural analysis, the structural elements of Cold Mountain film is connecting to each other to a whole unity that cannot be separated one another in order to support each other. The second is the psychoanalytic analysis that shows that problems of the major character are dominated by superego. The writer finds that Ada’s superego leads her to be uncommon woman.